2020
DOI: 10.1186/s12978-020-00973-0
|View full text |Cite
|
Sign up to set email alerts
|

A rapid scoping review of fear of infertility in Africa

Abstract: Background Fear of infertility (FOI) is often reported in studies about reproductive health but this literature not yet mapped. The aim of this rapid scoping review of qualitative studies was to describe the nature of FOI in Africa. Methods Eligibility criteria were qualitative data from Africa reporting views of women and men of any age. MEDLINE and CINAHL databases were searched for English language citations to February 2019 using keywords related to fear, infertility and Africa. Two independent reviewers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 47 publications
11
36
0
Order By: Relevance
“…None of the four interactions tests around age and having children were significant. To our knowledge, this is the first study to examine if this belief is quantitatively associated with actual contraceptive use despite calls to design interventions to address this misperception (Sedlander et al 2018;Diamond-Smith 2012;Boivin et al 2020;Marston and Francis 2019;Harper et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the four interactions tests around age and having children were significant. To our knowledge, this is the first study to examine if this belief is quantitatively associated with actual contraceptive use despite calls to design interventions to address this misperception (Sedlander et al 2018;Diamond-Smith 2012;Boivin et al 2020;Marston and Francis 2019;Harper et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In Boivin et al. ( 2020 )’s systematic review of fear infertility in Africa, authors found that the majority of studies reported that hormonal methods (e.g., injectables and oral contraceptives) would cause infertility. Only one study cited the perception that condom use could cause infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that the fear of infertility and its consequences may influence help-seeking behaviors in men, which may trigger diseases in later life ( 30 ). The experience of infertility may negatively impact on personal health behaviors ( 31 ) and in some contexts, it may hinder taking further actions to prevent health-related problems or seek appropriate treatments ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although fear of infertility, or other perceived side effects from contraception, are not addressed in this study, there is a growing body of literature around fear of side effects (including infertility) as a reason for contraceptive nonuse. We acknowledge that there may be a bidirectional relationship between contraceptive use and fear/belief that contraception may cause infertility (Figure 1) (Sedlander et al 2018;Huber-Krum and Norris 2020;Boivin et al 2020).…”
Section: Infertility-related Constructs and Contraceptive Usementioning
confidence: 99%